2012
DOI: 10.1007/s11999-012-2300-0
|View full text |Cite
|
Sign up to set email alerts
|

High 10-Year Survival Rate with an Anatomic Cementless Stem (SPS)

Abstract: BackgroundProximal cementless fixation using anatomic stems reportedly increases femoral fit and avoids stress-shielding. However, thigh pain was reported with the early stem designs. Therefore, a new anatomic cementless stem design was based on an average three-dimensional metaphyseal femoral shape. However, it is unclear whether this stem reduces the incidence of thigh pain.Questions/purposesWe asked whether this stem design was associated with a low incidence of thigh pain and provided durable fixation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…First, survival rates of recent THA implants are so high [6,12,31,34,35] that the number of hips and length of followup of this study are not sufficient to reveal the superiority of this implant. Although larger cohorts and longer followups would be necessary to confirm whether this implant enhances bone bonding and survival, it was associated with a high survival rate.…”
Section: Discussionmentioning
confidence: 84%
“…First, survival rates of recent THA implants are so high [6,12,31,34,35] that the number of hips and length of followup of this study are not sufficient to reveal the superiority of this implant. Although larger cohorts and longer followups would be necessary to confirm whether this implant enhances bone bonding and survival, it was associated with a high survival rate.…”
Section: Discussionmentioning
confidence: 84%
“…Compared with porous alone femoral stems, HA stems demonstrated better result with less adverse effects (Epinette and Manley 2008). Sariali et al (2012) reported that the survivalship of anatomic cementless stem (SPS) was 100% considering stem revision for aseptic loosening as the end point. Antonio Herrera et al reported their surgical experience with more than 4000 cementless hydroxyapatite coated hip prostheses (the ABG I and ABG II prosthesis an anatomical HA-coated stem with press-fit metaphyseal fixation, Stryker) since 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Although 10 year-to 16 year-survival rates have been reported with short stems [4,7,9], we need stronger evidence to determine whether short stems represent a safe alternative to traditional long-stem designs. It is my hope that a national joint registry, such as the American Joint Replacement Registry, and international joint registries, such as the Nordic Arthroplasty Register Association will help to confirm these findings, as well as determine the risk factors associated with shortstem THA failures.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The longest followup studies (10 years or longer) have been reported for short femoral implants either with a tight metaphyseal design [7,9] or with a neck-preserving concept [4,5], in patients with a mean age of 52 years to 73 years. Using these systems, researchers found acceptable stem revision rates (0% to 3.4%) for aseptic loosening [4,5,7,9].…”
mentioning
confidence: 99%